A Prospective Observational Study on Clinical Profile and Outcomes of Dilated Cardiomyopathy Patients in a Tertiary Care Center in Nepal - Mishra , Jeetendra Kumar; Keyal, Niraj Kumar; Karn, Achutanand Lal; Jha, Sudhakar; Gupta, Madhu; Ali, Imran (Med Phoenix, 2025)
Introduction: Dilated cardiomyopathy is the most common cause of congestive heart failure in patients with different cardiac insults. This study aims to explore the signs, symptoms, and outcome of dilated cardiomyopathy in the tertiary level of health care of Nepal. Materials and Methods: It was a prospective observational study in a cardiology department of the National Medical College, Birgunj. This study was conducted on 152 patients admitted to the cardiology department of the medical college. Demographic data was gathered from each patient in the performed sheet at the presentation time. Signs and symptoms, electrocardiographic and echocardiographic findings were also recorded. Patients’ outcomes were recorded in terms of mortality discharge toward, and leave against medical advice. The descriptive data are presented as the number and percentage for categorical data and mean ± standard deviation for continuous data according to their distribution. Results: One hundred and fifty-two patients were included in this study. 84(55.3%) were males and 68(44.7%) were females. Mechanical ventilation was used in 36.8% and inotropes in 73.0% of patients. Chest pain, cough, dyspnea, swelling of limbs, and palpitation were present in 8(5.26%), 27 (17.76%), 64 (42.1%), 29 (19.07%), 9(5.9%) of patients. Bilateral Infiltrates, Cardiomegaly, Normal, and Consolidation in left lower zone were present in 29 (19.07%) 107 (70.39%), 12 (7.89%), 4(2.63%) in our study. 98(64.5%) were discharged to home, 52(34.2%) expired and 2(1.3%) of patients underwent leave against medical advice. The use of inotropes, mechanical ventilation, and presence of cardiomegaly on chest x-rays was associated with mortality. Conclusion: The most common presentation was cough and basal crackles. Cardiomegaly, RS pattern with Left Bundle Branch Block, and global hypokinesia were the most common radiological presentations.